Analysis of the Effectiveness of Online Learning of Biology in Jayapura City State High Schools During the Covid-19 Pandemic for the Academic Year 2020/2021 - Vidya Murti Ningrum; Megawati, Ruth; Maik Akobiarek (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the effectiveness of online biology learning at Public High Schools in Jayapura City during the COVID-19 pandemic for the 2020/2021 academic year. This type of research is quantitative descriptive, with a population of 1,217 students. Sampling was carried out using a purposive sampling technique so that it was obtained. the total sample was 211 students. The instruments in this research used questionnaires and interviews. The questionnaire is in the form of written questions given directly or online to respondents. Meanwhile, interviews were conducted to strengthen the statements that had been answered in the previous questionnaire. The data was analyzed manually using the average formula according to Sudijono 2007 which will be confirmed with the Widoyoko 2010 range of values. The research results of the three indicators were obtained as follows: (1) online learning support components obtained an average score of 3.17 in the effective category, (2) the characteristics of online learning obtained an average score of 3.22 in the effective category, (3) the benefits of online learning obtained an average score of 3.04 in the effective category. Overall, the effectiveness of online learning obtained an average score of 3.15